Comparative Evaluation of Effect of Aloe Vera Gel (Aloe Barbadensis Miller) on Dentine Root Surface of Periodontally Involved Human Teeth: An Invitro Scanning Electron Microscopic Study Running title: Effect of Aloe vera Gel on Dentine Root Surface (International Journal of Environmental Sciences, 2025)
Periodontitis is characterised by inflammation of various components of the periodontium and produces substantial changes in the tooth and root surface which is referred to as a pathologically exposed root surface. As it prevents the creation of new attachments, the smear layer serves as a physical barrier between the root surfaces and periodontal tissues. Although the medicinal use of Aloe Vera has been reported, less literature is available regarding its use as root conditioning agent. The purpose of this study was to assess how Aloe Vera gel affected periodontally infected root surfaces. Thirty human teeth extracted because of chronic periodontitis were collected. Water and a soft-bristled brush were used to remove blood and saliva from the extracted teeth. The samples were categorized into test group (group 1) - Aloe Vera gel and control group (group 0)-placebo gel. Samples were prepared for histological analysis using Scanning Electron Microscopy (SEM). Thirty human teeth extracted because of chronic periodontitis were collected. Water and a soft-bristled brush were used to remove blood and saliva from the extracted teeth. The samples were categorized into test group (group 1) - Aloe Vera gel and control group (group 0)-placebo gel. Samples were prepared for histological analysis using Scanning Electron Microscopy (SEM). The number of patent dentinal tubules relative to the total number of dentinal tubules present was evaluated, as was the effectiveness of removing the smear layer. In comparison to the control group (0), the test group's smear layer efficacy was the highest (1.87). The highest number of patent dentinal tubules was seen in test group (5.13) than the control group (0). The present in vitro study concludes that Aloe Vera gel as a root conditioning agent to be more efficient in smear layer removal and exposure of dentinal tubules than placebo gel.